PENGARUH PENGGUNAAN MEDIA SMARTBOX TERHADAP HASIL BELAJAR SISWA PADA MATERI PERUBAHAN WUJUD BENDA DI MATA PELAJARAN IPAS KELAS IV SD NEGERI 58 PALEMBANG - Novi Nurhasanah; Nina Haifa Hafifah; Resti Ayu Ramadhani; Neng Fitri Lestari; Yusni Arni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine how the use of Smartbox media influences students’ learning outcomes on the topic of Changes in the States of Matter in the IPAS subject among fourth-grade students at SD Negeri 58 Palembang. The main issue in teaching IPAS lies in the abstract nature of the topic, which is difficult for students to understand without concrete learning media. This research employed a quasi-experimental method. The study involved 56 students who were divided into two groups of 28 each. The Experimental Group used Smartbox media, while the Control Group received instruction through conventional methods. Data were collected through pretest and posttest assessments, each consisting of 25 items. The analysis revealed a significant difference in the improvement of learning outcomes between the two groups (p = 0.000 < 0.05). The Experimental Group that used Smartbox achieved an average score of 19.61, while the Control Group obtained an average score of 5.21. The considerably higher improvement in the experimental group indicates that Smartbox media is more effective in enhancing learning outcomes compared to conventional approaches. Smartbox provides a positive and significant impact on students’ understanding of changes in the states of matter by offering direct, concrete, interactive, and enjoyable learning experiences that promote student engagement and enthusiasm. Therefore, it can be concluded that Smartbox media is effective in improving students’ achievement in the Natural and Social Sciences subject at the elementary school level.